KONSEP IE DALAM ORGANISASI SOSIAL MASYARAKAT JEPANG - Yuliani Rahmah (KIRYOKU, 2017)
[IE CONCEPTS IN SOCIAL ORGANIZATIONS JAPANESE SOCIETY] Ie System is a legacy of the ancestors of Japanese society that is passed down through generations in traditional Japanese families. This system is based on the character of Japanese society that is patrilineal with the concept of daikazoku. This Ie system is a kinship system that applies to traditional Japanese families. But the spirit and sense of kinship that imbued the Ie system can still be seen in today's society, both in the rural community and in the modern society living in urban areas. Ie system that prioritizes group togetherness rather than individuals is also reflected in the corporate management structure in  Japanese society. Representation of the Ie system is seen as a sense of ownership of employees to the company where they work. They regarded the company not only as a place to work but became the second home to provide welfare for them. It affects the attitude of those who prefer the company name on behalf of themselves as an individual.